2013
DOI: 10.1371/journal.pone.0071659
|View full text |Cite|
|
Sign up to set email alerts
|

The Effectiveness of Inodilators in Reducing Short Term Mortality among Patient with Severe Cardiogenic Shock: A Propensity-Based Analysis

Abstract: BackgroundThe best catecholamine regimen for cardiogenic shock has been poorly evaluated. When a vasopressor is required to treat patients with the most severe form of cardiogenic shock, whether inodilators should be added or whether inopressors can be used alone has not been established. The purpose of this study was to compare the impact of these two strategies on short-term mortality in patients with severe cardiogenic shocks.Methods and ResultsThree observational cohorts of patients with decompensated hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 33 publications
0
25
0
4
Order By: Relevance
“…[20][21][22][23][24][25][26] Despite these important caveats, patients with critically low CO generally cannot be stabilized medically without inotropic support, and inodilator therapy appears beneficial in cardiogenic shock. 27 In the absence of severe hypotension, an inodilator is preferred over an inoconstrictor for increasing CO due to more favorable effects on afterload, cardiac filling pressures, and myocardial blood flow. [28][29][30][31][32] Dobutamine Dobutamine augments myocardial contractility via strong B1R stimulation with mild to moderate B2R agonism and mild A1R agonism, producing a strong dose-dependent increase in SV and CO with moderate increases in HR and a variable effect on MAP (Tables 1 and 2).…”
Section: Goals Of Resuscitationmentioning
confidence: 99%
“…[20][21][22][23][24][25][26] Despite these important caveats, patients with critically low CO generally cannot be stabilized medically without inotropic support, and inodilator therapy appears beneficial in cardiogenic shock. 27 In the absence of severe hypotension, an inodilator is preferred over an inoconstrictor for increasing CO due to more favorable effects on afterload, cardiac filling pressures, and myocardial blood flow. [28][29][30][31][32] Dobutamine Dobutamine augments myocardial contractility via strong B1R stimulation with mild to moderate B2R agonism and mild A1R agonism, producing a strong dose-dependent increase in SV and CO with moderate increases in HR and a variable effect on MAP (Tables 1 and 2).…”
Section: Goals Of Resuscitationmentioning
confidence: 99%
“…In terms of background medication, patients on beta blockers theoretically respond better to levosimendan or milrinone, as these drugs act independently of the βadrenergic receptors; the same is true in the case of beta-1 receptor down-regulation that has been noticed in HF [34]. Concerning the hemodynamic status, in the presence of persistent hypotension, besides adequate volume status, norepinephrine is the vasopressor of choice and can be used in combination with vasodilating inotropes such as dobutamine and levosimendan in an effort to enhance cardiac contractility while maintaining adequate blood pressure for tissue perfusion; vasopressor may subsequently be withdrawn with the amelioration of cardiac performance [35]. The combination of two different classes of inotropes, in contrast, does not seem to provide additional benefit.…”
Section: Inotropes In Acute Heart Failurementioning
confidence: 94%
“…A propensity score-matched analysis by the GREAT network showed that combining vasopressors (epinephrine, norepinephrine, or dopamine) with vasodilating inotropes (dobutamine, levosimendan or PDE inhibitors) leads to better survival than vasopressors alone [35].…”
Section: Inotropes In Cardiogenic Shockmentioning
confidence: 99%
“…In one recent Cochrane systemic review assessing inotropic agents on CS, the included studies were of no milrinone treatment group [14]. Data from a large pooled retrospective analysis supported that the addition of an inodilator to vasopressors was associated with lower mortality, however, only 1% patients treated with PDE3 inhibitors [15].…”
Section: Introductionmentioning
confidence: 99%